Evaluating the effectiveness of sexual and reproductive health services during humanitarian crises: A systematic review - Singh, Neha S.; Smith, James; Aryasinghe, Sarindi; Khosla, Rajat; Say, Lale; Blanchet, Karl (PloS one, 2018)
An estimated 32 million women and girls of reproductive age living in emergency situations, all of whom require sexual and reproductive health (SRH) information and services. This systematic review assessed the effect of SRH interventions, including the Minimum Initial Service Package (MISP) on a range of health outcomes from the onset of emergencies. We searched EMBASE, Global Health, MEDLINE and PsychINFO databases from January 1, 1980 to April 10, 2017. This review was registered with the PROSPERO database with identifier number CRD42017082102. We found 29 studies meet the inclusion criteria. We found high quality evidence to support the effectiveness of specific SRH interventions, such as home visits and peer-led educational and counselling, training of lower-level health care providers, community health workers (CHWs) to promote SRH services, a three-tiered network of health workers providing reproductive and maternal health services, integration of HIV and SRH services, and men's discussion groups for reducing intimate partner violence. We found moderate quality evidence to support transport-based referral systems, community-based SRH education, CHW delivery of injectable contraceptives, wider literacy programmes, and birth preparedness interventions. No studies reported interventions related to fistulae, and only one study focused on abortion services. Despite increased attention to SRH in humanitarian crises, the sector has made little progress in advancing the evidence base for the effectiveness of SRH interventions, including the MISP, in crisis settings. A greater quantity and quality of more timely research is needed to ascertain the effectiveness of delivering SRH interventions in a variety of humanitarian crises.